Of America 1 : Readings for young Americans - Mayfield, H.; Hedquist, Marion (Pensacola, Fla. : Pensacola Christian College, 1985)
Stories, poems, essays, and biographical sketches examine American values, beliefs, and ideals.
"A Beka Book."
Includes bibliographical references and index.
Keywords: National characteristics, American -- Juvenile literature; National characteristics, American; United States -- Civilization -- Juvenile literature; United States -- Biography -- Juvenile literature; United States -- Civilization; United States -- Biography